Analisis Kandungan Logam Berat dan Mikroba Fungsional Pada Kascing Dari Campuran Kotoran Ayam, Bonggol Pisang dan Ampas Tahu - Tri Wahyu Aditya; Hilwa Walida; Yusmaidar Sepriani; Kamsia Dorliana Sitanggang (LPPM Universitas Al Asyariah Mandar, 2022)
The use of fertilizers containing heavy metals repeatedly and in the long term can lead to accumulation of heavy metals in the soil, while functional microbes are used to improve fertilization efficiency, fertility and soil health. This study aims to determine the content of heavy metals and the number of functional microbes found in vermicompost in agricultural soil. This research begins with the manufacture of worms that feed a mixture of chicken manure, banana weevil and tofu dregs. The vermicompost that had been taken were then analyzed for the content of Pb and Hg as well as the number of functional microbes. Sample analysis was carried out at the Laboratory of Soil Chemistry and Biology, Andalas University, Padang, West Sumatra. The results showed that the quality of the Hg content was 0.0884 ppm, the Pb content was 0.941 and the number of functional microbes was >1.1 x 108cfu/g. Based on the results of the analysis, it can be ascertained that the vermicompost from a mixture of chicken manure, banana weevil and tofu dregs has met the standards of SNI 19-7030-2004, so it is safe to be used as an organic product.